Effects of Emulsifier Type and Ingredient on the Foam Stability of Meringue - Bekti Wulan Sari; Afwa Hayuningtyas; Pinyapat Jitphongsaikul; Vishal Chherti; Alwani Hamad (Universitas Muhammadiyah Purwokerto, 2022)
Food foams provide texture and structure for many food products, such as meringues. Meringues, a fundamental of culinary arts, commonly consist of whipped egg white and sugar and have about most of the air phase. These types of composition allow for making different products with the same ingredients; thus, meringue design is essential to investigate foam stability and ability. This study aims to examine the foam stability of meringue using the different components such as protein as emulsifiers (egg white and gelatin) and the composition of sugars (icing and granule) on the foam stability and formation of meringue. Using gelatin as an emulsifier showed the foam more stable than egg white (>24 h), and adding the icing sugar with gelatin made the foam texture smoother. On the other hand, foam formation was faster when using emulsifier egg white, but stability was less than gelatin. The more stable foam produced by the combination of emulsifier and sugar ingredients would provide a better texture of meringue after baking, a smooth surface, no hole, and a more crunchy sweet taste. It was concluded that the composition of the ingredients and type of emulsifier would affect the stability and ability of foam, resulting in the character of the meringue after baking.